Effect of Heparin on Thrombin Inhibition in the Microcirculation - Nydahl, S; Frebelius, S; Swedenborg, J (Thrombosis and Haemostasis, 1993)
Disappearance of thrombin enzymatic activity was measured during recirculation through the microvasculature in a rat Langendorff heart preparation. This resulted in a 50% loss of thrombin from the recirculating solution. No increased loss of thrombin could be demonstrated if a mixture of antithrombin III and thrombin was recirculated, compared to thrombin alone. If, however, a heparin/thrombin mixture was recirculated, a 90% loss of thrombin could be demonstrated. Pretreating the microvasculature with large amounts of heparin resulted in recovery of antithrombin III in the recirculated heparin solution. At a subsequent recirculation with a heparin/thrombin mixture the loss of thrombin was decreased to the control level, as seen when recirculation with thrombin alone was performed. It is concluded that disappearance of thrombin enzymatic activity from a solution when recirculated through the microcirculation can be considerably increased if recirculated together with heparin, which probably reacts with endogenous antithrombin III on the vessel wall. The disappearance of thrombin in the absence of heparin was, however, unaffected by antithrombin III. The latter finding is compatible with the hypothesis that, in the microcirculation, antithrombin III/glycosaminoglycans play only a minor role for inhibition of thrombin coagulant activity and that thrombin binds mainly to thrombomodulin.